Retrospective Analysis of Inguinal Hernia in Pediatric Patients in a Tertiary Center, Misurata– Libya (Journal of Academic Research, 2025)
Background: Inguinal hernia repair is one of the most commonly performed operations and it is among the most frequent reasons for referral to pediatric surgery clinics. The incidence of inguinal hernia is 1-5% in the pediatric population and is even higher in premature babies, as high as 10-30%.Aim of the study: to analyze inguinal hernia distribution according to age, gender, side and associated congenital anomalies in the pediatric population.Materials and Methods: A descriptive retrospective study included all pediatric patients diagnosed as inguinal hernia and operated at pediatric surgery department in Misurata Medical Center during the year of 2022. Hospital records were reviewed, and patients' data were collected in terms of age, sex, site of hernia, presence of incarceration and congenital abnormality association.Results: 103 patients included in the study, 77 (74.8%) patients were males and 26 (25.2%) were females, with a female to male ratio 1:2.96. Age of patients ranged from 1 month to 14 years, with mean age of 2.9 years. Right side was affected in 51 patients (49.5%), while left side was 37 patients (35.9%), bilateral inguinal hernia was found in 15 patients (14.6%). Elective cases were 99 patients (96.1%), while urgent cases were 4 patients (3.9%) with diagnosis of incarcerated or strangulated hernia. 98 (95.1%) cases did not have any association, while associated conditions were undescended testis, hydrocele and umbilical hernia.
Keywords: inguinal hernia; pediatric surgery; indirect; incarceration